Synthesis of WC composite powder with nano-cobalt coatings and its application in WC-4Co cemented carbide. Issue 9 (15th June 2018) - He, Rengui; Wang, Jianying; He, Meng; Yang, Hailin; Ruan, Jianming
Abstract: Composite powder of tungsten carbide with nano-cobalt coatings was successful manufactured via a novel sol-gel process, and coarse grained WC-4 wt% Co cemented carbide was produced from the cobalt-coated WC powder. Phase composition and microstructure evaluation were investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The results revealed that the WC particles were completely encased in the CoC2 O4 layers by the sol-gel process. Core-shell structured WC-4 wt% Co composite powder was subsequently prepared by reducing the WC-CoC2 O4 precursor powder in hydrogen atmosphere. The morphology and crystal structure of the cobalt-coating were found to depend on the reduction temperature. Chemical analyses revealed that the WC-Co composite powders were non-contaminated and composition-controllable. WC-4 wt% Co cemented carbide fabricated from the cobalt-coated WC composite powder showed a refined and uniform microstructure, and therefore improved mechanical properties, compared to the cemented carbide made by ball-milled WC-Co powder. The transverse rupture strength was 2249 MPa in the cemented carbide from the cobalt-coated WC powder, compared to 1871 MPa of the carbide made by the ball-milling powder.